2016
DOI: 10.18404/ijemst.85479
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-service Science Teachers’ Mental Models for Concept of Atoms and Learning Difficulties

Abstract: The purpose of this study is to reveal the preservice science teachers' difficulties about the concept of atoms. The data was collected from two different sources: The Draw an Atom Test (DAAT) and face-to-face interviews. Draw an atom test (DAAT) were administered to the 142 science teacher candidates. To elaborate the results, the researcher conducted face-to-face interviews with 15 students. The students' drawings were analyzed and grouped into eight different categories. These categories were: 1-Rutherford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
5
20
0
3
Order By: Relevance
“…For argumentation skill factor, Calik and Kolomuc [33] suggested that combining different conceptual change methods such as argumentation with the teaching intervention could help students overcome alternative conceptions for chemistry concepts and that students were able to store their new knowledge in their long-term memories. This suggestion is line with the opinion from [46,47] who stated that argumentation is a fundamental discourse of science, a part of the practice of science for developing, evaluating, and refining, scientific theories about the natural world. For multiple representation competences factor, Hilton and Nichols [38] presented that the development of an understanding of the form of individual multiple representation competences is an important step in helping chemistry students interpret them.…”
Section: Discussionsupporting
confidence: 81%
“…For argumentation skill factor, Calik and Kolomuc [33] suggested that combining different conceptual change methods such as argumentation with the teaching intervention could help students overcome alternative conceptions for chemistry concepts and that students were able to store their new knowledge in their long-term memories. This suggestion is line with the opinion from [46,47] who stated that argumentation is a fundamental discourse of science, a part of the practice of science for developing, evaluating, and refining, scientific theories about the natural world. For multiple representation competences factor, Hilton and Nichols [38] presented that the development of an understanding of the form of individual multiple representation competences is an important step in helping chemistry students interpret them.…”
Section: Discussionsupporting
confidence: 81%
“…Bu araştırmanın sonuçları bağlamında düşünüldüğünde, öğretmenlerin etkili bir teknoloji entegrasyonu için verilecek olan hizmet içi eğitimlerde direk olarak teknoloji odaklı bir yaklaşım yerine AB ve PAB'ı da kapsayan aşamalı bir model önerilebilir. Örneğin hizmet içi eğitim kapsamında atom konusunu öğretecek fen öğretmenlerine atom ile ilgili kavramsal çerçevede yer alan ve öğrencilerin zihinlerinde var olabilecek modeller detaylı olarak öğretilebilir (Kiray, 2016b). Alan bilgisine hâkim olan öğretmene daha sonra bu konunun hangi öğretim yöntem ve teknikleri (drama, rol yapma vb.)…”
Section: Sonuç Ve öNerilerunclassified
“…When studies on mental models in chemistry are examined, it is seen that studies on chemical bonding (Taber, 1998;Taylor & Coll, 2002), atomic structure (Adbo & Taber, 2009;Akaygün, 2016;Çökelez & Dumon, 2005;Çökelez & Yalçın, 2012;Harrison & Treagust, 1996;Kıray, 2016;Polat, 2012;Zarkadis, Papageorgiou, & Stamovlasis, 2017), acids, acid strength and bases (McClary & Talanquer, 2011;Çelikler & Harman, 2015), particle nature of matter (Demircioğlu, Vural, & Demircioğlu, 2013) and vapor pressure (Tümay, 2014) are common. Taber (1998) has found that the mental model students prefer for covalent compounds is simple octet rule.…”
Section: Research Focusmentioning
confidence: 99%
“…In mental model studies associated with structure of the atom, Bohr atom model has been identified as the dominant mental model among students. Kıray (2016) has stated that Bohr atom model hinders students' learning of quantum structure of the atom. It has been established that students visualized the atom as round, ball or sphere, and as hard or solid.…”
Section: Research Focusmentioning
confidence: 99%